Understanding stakeholder conflict between conservation and hunting in Malta. (November 2015) - Veríssimo, Diogo; Campbell, Brian
Abstract: Conservation conflicts often involve tensions between human stakeholders. One highly topical conflict is that around migratory bird hunting in the Mediterranean, particularly in Malta. Here, tensions between hunters and anti-hunting groups have escalated to include rural surveillance operations by anti-hunting groups, physical scuffles with hunters, retaliatory poaching and measures unheard of in Europe, such as the use of drones or army interventions. We describe the historical and political background to the Maltese conflict and use social network analysis to map the institutional relationships between governmental and non-governmental stakeholders influencing hunting in Malta. Our analysis confirms that the institutional landscape is highly polarised with two distinctive sides with few links between them. Nonetheless there are links between organisations in opposite sides of the spectrum and these could be explored to improve dialogue between the hunting and anti-hunting lobby. We also uncover that the ORNIS committee, the state's single hunting consultative platform lacks brokering power, the ability to connect otherwise unconnected groups within a network, which is likely why those opposed to spring hunting have recently started campaigning for a national referendum on the issue. Although independent monitoring is urgently needed around the Mediterranean, if science is to contribute to the management of this conflict, it will only be useful if the current stakeholder polarisation is overcome. Important steps towards conflict resolution include anti-hunting groups improving their ability to distinguish clearly between species conservation and animal welfare, and the ability of hunting groups to co-ordinate themselves better to ensure compliance with the law amongst their membership. Highlights: The institutional landscape around hunting is highly polarised. ORNIS governmental platform lacks brokering power to address the hunting conflict. The high brokering power of BirdLife Malta explains its recent push for a referendum. There is high heterogeneity amongst both hunting and conservation groups.